Analysis of Learning Volleyball Passing Skills at SMAN 1 Muara Sugihan - Anggraini, Dia; Wardiah, Dessy; Lanos, Muhsana El Cintami (PPSDP International Journal of Education, 2024)
This study aimed to find out the results of teaching basic techniques of bottom passing in volleyball games to students of SMAN 1 Muara Sugihan. This study was quantitative descriptive. The population in this study was class X students at State High School 1 Muara Sugihan, with sampling using purposive sampling techniques, by paying attention to the criteria of students who understand basic techniques in volleyball, totaling 30 students. The data collection technique used in this study is a volleyball bottom passing skill test. The data analysis technique used descriptive statistical analysis techniques. The results of the data analysis conducted in the study showed that of the 20 students who participated in volleyball learning at State High School 1 Muara Sugihan, the students’ volleyball passing skills were in the sufficient category, with an average score of 40.50 and a percentage of 48%. It can be concluded that the skills in learning volleyball bottom passing in the students of State High School 1 Muara Sugihan were in the sufficient category, so there is a need for development in learning to pass under volleyball.